Dosimetric characterization of carbon fiber stabilization devices for post-operative particle therapy. (December 2017) - Mastella, E.; Molinelli, S.; Magro, G.; Mirandola, A.; Russo, S.; Vai, A.; Mairani, A.; Choi, K.; Fiore, M.R.; Fossati, P.; Cuzzocrea, F.; Gasbarrini, A.; et al.
Highlights: Carbonaceous implants do not cause appreciable artifacts on CT images. Carbonaceous devices cause slight perturbation on TPS dose calculation accuracy. A precise modeling and material assignment of the device should always be performed. Multiple beams and avoidance structures are recommended with metallic implants. Abstract: Purpose: The aim of this study was to evaluate the dosimetric impact caused by recently introduced carbon fiber reinforced polyetheretherketone (CF/PEEK) stabilization devices, in comparison with conventional titanium (Ti) implants, for post-operative particle therapy (PT). Methods: As a first step, protons and carbon ions Spread-Out Bragg Peaks (SOBPs) were delivered to CF/PEEK and Ti screws. Transversal dose profiles were acquired with EBT3 films to evaluate beam perturbation. Effects on image quality and reconstruction artifacts were then investigated. CT scans of CF/PEEK and Ti implants were acquired according to our clinical protocol and Hounsfield Unit (HU) mean values were evaluated in three regions of interest. Implants and artifacts were then contoured in the sample CT scans, together with a target volume to simulate a spine tumor. Dose calculation accuracy was assessed by comparing optimized dose distributions with Monte Carlo simulations. In the end, the treatment plans of nine real patients (seven with CF/PEEK and two with Ti stabilization devices) were retrospectively analyzed to evaluate the dosimetric impact potentially occurring if improper management of the spine implant was carried out. Results: As expected, CF/PEEK screw caused a very slight beam perturbation in comparison with Ti ones, leading to a lower degree of dose degradation in case of contouring and/or set-up uncertainties. Furthermore, CF/PEEK devices did not determine appreciable HU artifacts on CT images thus improving image quality and, as a final result, dose calculation accuracy. Conclusions: CF/PEEK spinal fixation devices resulted dosimetrically more suitable than commonly-used Ti implants for post-operative PT.